Proposta de guia prático para o cumprimento dos Objetivos de Desenvolvimento Sustentável nas empresas da construção civil, a partir de pesquisa exploratória em amostra de construtoras na região de São Carlos – SP-Brasil - Rocha, Gabriel Pilegis (Universidade Federal de São Carlos, 2022)
Since 2015, the Sustainable Development Goals (SDGs) have had a major impact on government agendas, as well as on business, in the analysis and measurement of sustainable development in countries and cities. Therefore, it is a tool that can provide guidelines to promote sustainability to buildings. In civil construction, monitoring compliance with the SDGs is a little explored topic, however, this monitoring reports are essential to identify opportunities for improvement and innovation. In this research, a field study will be carried out with the construction companies of São Carlos/SP - Brasil, and will examine the compliance with the SDGs and the contribution of civil construction to the sustainability of the cities. For achieve this goal, the methodology adopted consists mainly on two strategies: the development and application of a survey about compliance with the SDGs in construction companies; and the elaboration of a practical guide, comprising a framework of sustainable actions to stimulate the sustainable development in civil construction. Then, the results obtained were interpreted graphically. Therefore, despite a low adhesion to the methodology adopted in this study, it was possible to verify a partial compliance of the SDGs for civil construction in São Carlos. These data point to SDG 12 as the most performed while the SDG 7 was the lower, as well as it was observed that the SDG 10 and 16 weren’t widely accepted as relevant topics to civil construction sustainable development. Finally, through the practical guide to sustainable actions for progress in compliance with the SDGs, there were identified 107 sustainable practices to the civil construction.
Proposal of a practical guide for the fulfillment of the Objectives of Sustainable Development in civil construction companies, the from exploratory research in a sample of construction companies in the São Carlos region – SP-Brazil
Keywords: Objetivos de desenvolvimento sustentável (ODS); Construção civil; Sustentabilidade; Sustainable development goals (SDG); Civil construction; Sustainability; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL